Interaction between renal function and percutaneous edge-to-edge mitral valve repair using MitraClip. Issue 2 (February 2017) - Kaneko, Hidehiro; Neuss, Michael; Schau, Thomas; Weissenborn, Jens; Butter, Christian
Abstract: Background: MitraClip (MC; Abbott Vascular, Menlo Park, CA, USA) is a treatment option for mitral regurgitation. Renal dysfunction is closely associated with cardiovascular disease. However, the influence of renal function in MC remains not fully understood. In this study, we aimed to clarify the association between renal function and MC. Methods and results: We examined 206 consecutive patients who underwent MC and divided patients into 3 groups according to estimated glomerular filtration rate (eGFR), normal eGFR (≥60 mL/min/1.73 m 2 ) ( n  = 70), mild chronic kidney disease (CKD) (30–59 mL/min/1.73 m 2 ) ( n  = 106), and severe CKD (<30 mL/min/1.73 m 2 ) ( n  = 30). N-terminal pro-B type natriuretic peptide (NT-pro BNP) levels increased with decreasing eGFR. Kaplan–Meier curves revealed that the long-term survival rate significantly decreased with eGFR. After adjustment with the covariates, severe CKD was still associated with mortality. Improved renal function was observed in 30% and associated with baseline lower NT-pro BNP levels. Patients with improved renal function had higher chronic phase survival rate. Conclusion: Renal dysfunction is common in MC patients and the survival rate decreased with eGFR in association with increased NT-pro BNP levels. MC may improve renal function in approximately 30% of MC patients. Improved renal function is associated with lower NT-pro BNP levels and results in satisfactory prognosis. These results implies a close association between renal function and MC treatment.